Honeybee (Apis mellifera L.) Foraging on some Onion Cultivars and its Relation with their Nectar Quantity and Quality - S. Seyedebrahimi; R. Ebadi; M. Mobli; B. Hatami (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2004)
In order to study the nectar quantity and quality of some onion cultivars and honeybees foraging activity on them, a complete randomized block design with three replications was conducted. Ten selected onion cultivars consisting of Ghom, Kashan, Azarshahr, Dorcheh, Tarom, Kazeroon 1, Kavar, Abarkooh, Hurand, and Yellow Sweet Spanish were used. Sixty mm mother bulbs of different onion cultivars were planted in 3×4 m plots on 6 lines. The distance between rows was 35 cm and plants were spaced 25 cm apart on each row. At flowering time, bees’ activity on the inflorescences was studied and flower nectar was collected in 10 micro-liter capillary tubes. Nectar volume was determined and analyzed. Mean numbers of honeybees visiting on inflorescence every 10 minutes and the mean residing time of each honeybee on a seed stalk (inflorescence) were significantly different in different cultivars. Hurand flowers had the least number of visitors and Dorche flowers had the longest visiting time. The amount of nectar varied in different cultivars, so did glucose (G), fructose (F), and sucrose (S) contents. Except for the Abarkuh cultivar that had more glucose than it had other sugars, all the cultivars had higher quantities of fructose than they had other sugars while sucrose had the least quantities among the sugars. Nectar sugar ratio in most of the cultivars was hexose dominant, which was identified by the low S/(F+G) ratio. Potassium, calcium, and sodium contents in nectar were different in different cultivars, too. Finally, the results showed that foraging activity of honeybees on onion inflorescences depends on the interactions of several factors such as nectar quantity and, more importantly, on sugar quantity and ratio as well as potassium content. .